An innovative approach to support social groupwork - Lee, Cheryl D.; Montiel, Eliette del Carmen; Atchison, Jamie; Flory, Paul; Liza, Jessica; Valenzuela, John (Groupwork, 2012)
This article discusses a creative endeavor to establish a university social groupwork club affiliated with the Association for the Advancement of Social Work with Groups, an international professional association. The club’s purposes were: 1) to nurture social groupwork; 2) to engage students, practitioners and academics in a collaborative groupwork experience, and; 3) to link members to an international social work organization that supports all aspects of groupwork. The planning, stages, mutual aid and evaluation of the club are described. A longitudinal survey design was used to evaluate members’ perceptions of the club. Feedback questionnaires (N = 129) were analyzed for a one-year period. Results indicated that club members benefited from mutual aid and experienced professional growth.